ANTIOXIDANT ACTIVITY, MOSQUITOCIDAL ACTIVITY, ANTIBACTERIAL ACTIVITY OF SOLVENT EXTRACT AND SYNTHESIZED NANOPARTICLES OF CLAUSENA EXCAVATA (BURM.) F. (RUTACEAE) AGAINST SELECTED MOSQUITOES AND PATHOGENIC BACTERIA - Jagadeesan, Yazhini; Kuppusamy, Elumalai (LIFE: International Journal of Health and Life-Sciences, 2019)
In the present investigation, Clausena excavata an indegeous plant was sequentially extracted with hexane, ethyl acetate and methanol and their bio efficacy in terms of Antioxidant activity, mosquitocidal activity and antibacterial activity was tested. Among the three-extract methanol extract of C. excavata displayed significant antioxidant, larvicidal, ovicidal, pupicidal activities against Aedes aegypti and Culex quinquefasciatus. Similarly, methanol extract also showed pronounced antibacterial activity against the selected human pathogenic bacteria. Thus, the methanol extract of C. excavata was used to synthesize silver mediated nanoparticles and its (C. excavata AgNPs) bio efficacy was also tested with the selected vector mosquitoes and selected human pathogenic bacteria. This present investigation envisages the possible utilization of C. excavata as a potent candidate as green pesticides in the near future.